PERBANDINGAN PENDAPATAN PETANI PADI SISTEM TANAM JAJAR LEGOWO DAN SISTEM TANAM HAZTON DI KELURAHAN TA’, KECAMATAN TANETE RIATTANG KABUPATEN BONE - Khaeriyah Darwis (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
This study aims to: (1) Total cost and acceptance rice farming which uses the system of planting Jajar Legowo with Hazton planting system; (2) Analyze the rice farming income ratio that uses Jajar Legowo planting system with Hazton planting system; and (3) Constraints faced by farmers in the Ta’ village of the Tanete Riattang Sub-District, especially combined farmers group which is SIPATOKKONG in transition Jajar Legowo Planting System to Hazton System. Determination of the respondents using Proportional Random Sampling method is 15% taken from each population that is 30 respondents to Jajar Legowo planting system and 30 respondents of Hazton system. The results showed that farm income using Jajar Legowo planting system is Rp.19.865.000 / 1 hectare / planting season and Hazton system is Rp 26.067.000 / 1 hectare / planting season. The result of t-test shows that the income of farming system of Hazton Planting System is significantly different by using Jajar Legowo Planting System. Based on the findings in this study, Cooperation between government and farmers in their respective fields will accelerate Indonesia's dream of becoming a world food barn. Farmers with a myriad of cultivation experiences concentrate on increasing productivity, while the government prepares regulations and regulations to ensure the sustainability of cultivation and distribution of crops produced by farmers. The government requires a significant increase in production, so the government must also protect farmers from the price fluctuations arising from price reductions during harvest time.